The influence of simulated rainfall on the removal of retained particulate matter on the surface of lawn grass leaves - Wang, Junrui; Kong, Weihan; Li, Haimei; Liu, Yu; Guo, Xiao (Frontiers in Plant Science, 2025)
Rainfall can wash the surface atmospheric particulate matter (PM) into the soil, and restore the PM retention function of the turfgrass blades. The dynamic process of PM removal on turfgrass blades concerning rainfall intensity and duration was investigated, and the relationship between rainfall, leaf surface structure, and the rate of foliar PM removal was established. Seven turfgrass species (Liriope spicata, Lolium perenne, Festuca elata, Poa pratensis, Zoysia sinica, Cynodon dactylon and Agrostis stolonifera) were examined in simulated rainfall experiments with total rainfall amounts of 16 mm, rainfall intensities of 10, 15, and 20 mm·h–1, and sampling intervals of 12, 8, and 6 min, respectively. The highest wash-off rates for foliar TSP, PM>10, PM2.5-10, and PM2.5 among the test plants were 84.05%, 87.99%, 78.62%, and 79.31%, respectively, with Liriope spicata and Zoysia sinica exhibiting higher wash-off rates. Higher rainfall intensity led to greater wash-off rates, requiring less time to reach maximum wash-off rates. It is important to note that rainfall did not completely remove foliar PM, and PM retention after 20 mm· h–1 rainfall was lower than that after 10 mm· h–1 rainfall. Additionally, particulate wash-off rates decreased with the increase in groove width, leaf hair length, and leaf hair width in the leaf surface structure. The present study provides a scientific foundation for quantitative investigations into PM removal by garden plants and offers guidance for selecting urban greening plants.